Investigation of resolution effects using a specialized diffusion tensor phantom - Bach, Michael; Fritzsche, Klaus H.; Stieltjes, Bram; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2014)
Purpose The clinical potential of the diffusion imaging-based analysis of fine brain structures such as fornix or cingulum is high due to the central role of these structures in psychiatric diseases. However, the quantification of diffusion parameters in fine structures is especially prone to partial volume effects (PVEs). Methods In this study, a phantom for the investigation of PVEs and their influence on diffusion parameters in fine structures of different diameter is presented. The phantom is produced by winding wet polyester fibers onto a spindle. The resulting fiber strands have well defined square cross-sections of 1-25 mm2 and provide a homogeneous and high fractional anisotropy (FA ≈ 0.9). Results Several PVEs are demonstrated and analyzed. It is shown that inferred results such as the fiber geometry and diffusion parameters strongly depend on the relative position of the structure of interest to the voxel-grid. Several implications of PVEs on post-processing methods such as Tract-based Spatial Statistics and fiber tractography are demonstrated. Conclusion These results show that the handling of PVEs in common post-processing tasks can be problematic, and that the presented phantom provides a valuable tool for the improvement and evaluation of these effects. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: DTI; fiber tracking; partial volume effects; resolution phantom; TBSS